Combustion of Torrefied Pellets of Furniture Work Dusts as Blends With Lignite - Yilgin, Melek; Hos, Bedriye; Pehlivan, Dursun (Asme, 2021)
In this study, torrefaction of pellets formed from furniture work dusts collected as a part of space cleaning actions in the industry has been examined. Burning behavior of torrefied dusts and lignite blends was studied. Torrefaction experiments were done under a nitrogen atmosphere for 1 h at temperatures of 220, 260, and 300 degrees C which corresponded to light, mild, and severe torrefaction, respectively. Combustion of blend pellets prepared by adding lignite in specific ratios to powders of torrefied pellets was carried out at 700 degrees C initial temperature using a vertical furnace system through which air was flowing in natural convection. Ignition times of blend pellets were affected by volatile matter and moisture contents. Volatile matter combustion rates were lower than those of raw waste, and accordingly, combustion times were higher. However, no relation between volatile matter combustion rates and times was observed. Blending raw or torrefied furniture work dusts with lignite have significantly influenced volatile matter and carbon combustion periods. There was no relation between carbon combustion rates and times. It was concluded that blend pellets of mild or severe torrefaction products of furniture work dusts and lignite behaved similarly to lignite during combustion.
Keywords: furniture work dust; pellet; torrefaction; lignite; co-combustion; energy from biomass; fuel combustion; renewable energy